Sclerosing cholangitis-like changes in hepatobiliary tuberculosis - Yasemin ÖZİN and Erkan PARLAK and Zeki Mesut Yalın KILIÇ and Tülay TEMUÇİN and Nurgül Şaşmaz (Turkish Journal of Gastroenterology, 2019)
-